2012
DOI: 10.1021/jm200799p
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting of Histone Deacetylase and Topoisomerase II with Novel Bifunctional Inhibitors

Abstract: Strategies to ameliorate the flaws of current chemotherapeutic agents, while maintaining potent anticancer activity, are of particular interest. Agents which can modulate multiple targets may have superior utility and fewer side effects than current single-target drugs. To explore the prospect in cancer therapy of a bivalent agent that combines two complimentary chemo-active groups within a single molecular architecture; we have synthesized dual-acting histone deacetylase and topoisomerase II inhibitors. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 68 publications
2
80
0
1
Order By: Relevance
“…Research supported the fact that topoisomerase I and HDAC inhibitors act synergistically promoting apoptosis in the cancer cells (Johnson et al, 2001;Marchion et al, 2004;Tsai et al, 2000) and both these inhibitors have been found to be concentrated in the nucleus to a higher therapeutic level (Chauhan and Kumar, 2013;Guerrant et al, 2012). On the similar lines, Guerrant et al evaluated and synthesized dual inhibitors (Fig.…”
Section: Figmentioning
confidence: 90%
“…Research supported the fact that topoisomerase I and HDAC inhibitors act synergistically promoting apoptosis in the cancer cells (Johnson et al, 2001;Marchion et al, 2004;Tsai et al, 2000) and both these inhibitors have been found to be concentrated in the nucleus to a higher therapeutic level (Chauhan and Kumar, 2013;Guerrant et al, 2012). On the similar lines, Guerrant et al evaluated and synthesized dual inhibitors (Fig.…”
Section: Figmentioning
confidence: 90%
“…Based on the therapeutic relevance of anthracyclines and on the synergistic antitumour effects of topo II and HDAC inhibitors, derivatives of daunorubicin linked to SAHA were designed as bifunctional agents [25]. Compounds of this series (7) exhibit cytotoxic activity comparable to daunorubicin, in spite of the in vitro inhibitory activity towards HDAC1 and HDAC6 similar to SAHA.…”
Section: Hybrid Compounds Incorporating Cytotoxic Moieties and Hdac Imentioning
confidence: 99%
“…Platinum(IV) complexes [50] were designed as dual-targeting prodrugs following the introduction of the vitamin E analogue, atocopherol succinate (a-TOS), as the axial ligand(s) of platinum(IV) (25). In this conjugate the platinum is expected to cause DNA damage, while a-TOS disrupts Bcl-xL-Bax interactions leading to mitochondrial dysfunction, thus enhancing the intrinsic mitochondria-mediated pathway of apotosis activated by DNA damage.…”
Section: Bifunctional Agents With Cleavable Linkersmentioning
confidence: 99%
“…They found that many of these hybrid compounds more potently inhibited HDAC and Topo II activities compared to SAHA and daunomycin --standard HDACi and Topo II inhibitors, respectively. Additionally, a subset of these compounds exhibited potent whole-cell anti-proliferative activities against representative cancer cell lines [13]. More recently, the same group designed and synthesised dual-acting topoisomerase I (Topo I)--HDAC inhibitors, which displayed potent antiproliferative activity as well [14].…”
Section: Introductionmentioning
confidence: 99%